Readiness to change is a predictor of reduced substance use involvement: Findings from a randomized controlled trial of patients attending South African emergency departments - Myers-Franchi, Bronwyn; van der Westhuizen, C.; Naledi, T.; Stein, D.J.; Sorsdahl, K. (BMC, 2016)
Background: This study examines whether readiness to change is a predictor of substance use outcomes and explores factors associated with RTC substance use among patients at South African emergency departments.